The Role of Information and Communication Technology (ICT) in Payroll Operations for Polytechnics in Nigeria - Bakari, Akilu (Asian Journal of Computing and Engineering Technology, 2023)
Purpose: Payrolling of staff in polytechnics lays significance on prompt rewards and productivity. Payment of salary in polytechnics is a key to performance effectiveness, efficiency and service success. This work discusses the role of Information and communication technologies (ICT) in payroll operation for polytechnics in Nigeria. Methodology: This research adopted qualitative method, it focus more on secondary date for analysis. The used of newspapers, journal, policy document and other relevant material was employed for the data collection. Findings: Information and communication technologies (ICT) refer to several forms of information exchange between two or more computers through any of the several methods of interconnection. These technologies provide speedy, low-cost and convenient means of communication. The adoption of these technologies in polytechnics in Nigeria federal and state government have been found to have direct positive impact on the institutions efficiency and have led to more rapid acceleration of development in the country. Technology is transforming human resource (HR) practices and activities by improving their effectiveness in managing organizational resources. Unique Contribution to Theory, Practice and Policy: The use of relevant technology in HR would increase organizational ability to meet new challenges such as globalization and increase of diversity in workplaces. Computerized payroll system is one of the technologies commonly used in HR and measured as the heart of HR activities. Utilization of Information Technology (IT) is now entered in a very good condition that can be used in every aspect of life. Utilization of good IT will generate benefits for its users in utilizing IT.